Elucidating the capacitive behavior of Gd-doped BNT-BKT-BT electrodes in All-in-One supercapacitor devices - Buldu-Akturk, Merve; Gozuacik, Namik Kemal; Aleinawi, Mohamad Hasan; Rostas, Arpad Mihai; Alkoy, Sedat; Mensur, Ebru; Erdem, Emre (Iop Publishing Ltd, 2023)
Bi0.5Na0.5TiO3-Bi0.5K0.5TiO3-BaTiO3 (BNT-BKT-BT) ceramics having various amounts of Gd-ions were synthesized via the solid-state reaction method. The electrochemical performance analysis of the Gd-doped BNT-BKT-BT ceramics has shown that the doping amount considerably impacts the BNT-BKT-BT electrode's electrochemical performance. The analysis of the defect centers was carried out using EPR spectroscopy. The samples showed paramagnetic defects in the EPR analysis. The 0.001 mol% Gd-doped BNT-BKT-BT showed a maximum signal intensity with partly resolved hyperfine lines, reaching the highest specific capacitance value of 612 Fg(-1). The EPR results were compared with the prototype BaTiO3 perovskite ceramic and concluded that the BNT-BKT-BT system has an extremely large strain, which hinders determining the spin-Hamiltonian parameters such as crystal field and hyperfine due to inhomogeneous line broadenings.
Keywords: BNT-BKT-BT ceramics; supercapacitors; EPR spectroscopy; gadolinium